Greatly improvement of Cr(VI) reduction by introducing foreign electrons and suppressing oxidization toward the reductant decimeter-sized zero-valent iron plate. Issue 2 (April 2023) - Liang, Yuheng; Chen, Fuming; Gao, Xingsen; He, Junfeng; He, Guannan; Wang, Yinzhen; Li, Wei; He, Qinyu
Abstract: A large-sized zero-valent iron plate (LSZVIP) with excellent reaction efficiency and cycle performance for heavy-metal ion removal from wastewater is desirable. However, it has yet to be achieved due to its relatively low specific surface area and non-crystal oxide shells produced during treatment, preventing its core electrons from transporting to the shell surface for heavy-metal ion reduction. Therefore, we proposed a novel mechanism to address the challenges in this paper by earthing the iron plate and stirring the treated solution to trigger an insulator-to-metal transition in the non-crystal oxides shell, thereby removing the barrier to electron transport in the oxide shells. Furthermore, earthing of the iron plate allows electrons from the earth to participate in hexavalent chromium (Cr(VI)) reduction, thereby eliminating the production of oxide shells during the reduction. With the stirring and earthing strategy, an acceptable Cr(VI)-reduction performance is obtained over the decimeter-sized zero-valent iron plate (DSZVIP). The residence time of earthing DSZVIP in the 1st cycle is 25 min and 80 min in the 10th cycle by stirring at 350 rotations per minutes (rpm) to achieve 100% Cr(VI)-reduction. This study provides a novel and applicable method for treating heavy-metal wastewater on a large scale. Highlights: Utilizing a decimeter-sized zero-valent iron plate (DSZVIP) to reduce Cr(VI) and obtain an satisfactory Cr(VI)-reduction performance for application, including high reduction efficiency and good cycle performance, through two strategies: stirring Cr(VI) solution and earthing the DSZVIP. Drive an insulator-to-metal transition in the non-crystal iron oxide shell of DSZVIP for the reduction of heavy metal ions by stirring. Earthing the DSZVIP for improving the Cr(VI)-reduction cycle performance since stirring could trigger an insulator-metal transition in non-crystal oxides shell, thus removing the obstacle of electrons-transportation in oxides shell. Earthing of iron plate introduce electrons from the earth to participate Cr(VI) reduction of and therefore eliminates the production of oxide shell during Cr(VI) reduction.